KONSEP PENDIDIKAN DALAM AJARAN AGAMA HINDU DI ERA DIGITAL - Putu Subawa (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2020)
The concept of Hindu education requires structuring. The structure of the concept of Hindu education provides clear guidance and references. What is Hindu Religious Education, how Hindu Religious Education is carried out effectively and efficiently, how to assess the level of achievement of Hindu Religious Education. A form of intelligent nation life is a social order that is protected from all forms of poverty and the ignorance of both personal and collective life, progressing, prosperity and spiritual birth. For this reason, education must be functional to have meaning for students and the community, evident in daily life. able to naturally encourage the growth and development of each student towards cultured adult humansKeywords: Education, Hinduism, Digital